Pengaruh Efikasi Diri terhadap Pemahaman Bacaan pada Mahasiswa Perguruan Tinggi - Elisa, Lusi (CV. Creative Tugu Pena, 2024)
This study aims to investigate the influence of self-efficacy on reading comprehension abilities among college students at IAI Tulangbawang. Using a qualitative approach, the research involved structured interviews and observations to gain in-depth insights into students' perceptions and experiences regarding self-efficacy and reading comprehension. The findings revealed a significant relationship between self-efficacy and reading comprehension abilities, wherein students with higher levels of self-efficacy tended to have better reading comprehension skills. These findings highlight the importance of developing self-efficacy to enhance students' academic literacy. The study also underscores the significance of qualitative approaches in understanding complex psychological phenomena such as self-efficacy and reading comprehension. However, the study has limitations and requires further research to validate the findings and deepen the understanding of the relationship between self-efficacy and reading comprehension at the college level. Thus, this research provides valuable insights for educational practitioners in developing effective intervention strategies to improve college students' reading comprehension abilities. Keywords: Self-efficacy, Reading Comprehension, College Students